Ca(2+)-Permeable Channels in the Plasma Membrane of Arabidopsis Pollen Are Regulated by Actin Microfilaments - Wang, Yong-Fei (Plant Physiol, 2004)
Cytosolic free Ca(2+) and actin microfilaments play crucial roles in regulation of pollen germination and tube growth. The focus of this study is to test the hypothesis that Ca(2+) channels, as well as channel-mediated Ca(2+) influxes across the plasma membrane (PM) of pollen and pollen tubes, are regulated by actin microfilaments and that cytoplasmic Ca(2+) in pollen and pollen tubes is consequently regulated. In vitro Arabidopsis (Arabidopsis thaliana) pollen germination and tube growth were significantly inhibited by Ca(2+) channel blockers La(3+) or Gd(3+) and F-actin depolymerization regents. The inhibitory effect of cytochalasin D (CD) or cytochalasin B (CB) on pollen germination and tube growth was enhanced by increasing external Ca(2+). Ca(2+) fluorescence imaging showed that addition of actin depolymerization reagents significantly increased cytoplasmic Ca(2+) levels in pollen protoplasts and pollen tubes, and that cytoplasmic Ca(2+) increase induced by CD or CB was abolished by addition of Ca(2+) channel blockers. By using patch-clamp techniques, we identified the hyperpolarization-activated inward Ca(2+) currents across the PM of Arabidopsis pollen protoplasts. The activity of Ca(2+)-permeable channels was stimulated by CB or CD, but not by phalloidin. However, preincubation of the pollen protoplasts with phalloidin abolished the effects of CD or CB on the channel activity. The presented results demonstrate that the Ca(2+)-permeable channels exist in Arabidopsis pollen and pollen tube PMs, and that dynamic actin microfilaments regulate Ca(2+) channel activity and may consequently regulate cytoplasmic Ca(2+).